Communication Anxiety Management in Islamic Missionary Organizations: A Literature Study on Communication Effectiveness in the Hyperconnectivity Era - Ahmad Sofian; Suhaily Amri Hasibuan; Anang Anas Azhar; Elfi Yanti Ritonga; Muhammad Randicha Hamandia; Zhila Jannati (Indonesian Journal Publisher, 2026)
The contemporary world creates challenges for Islamic preachers due to constant global connectivity and the rapid circulation of false information. This study examines how da’wah communicators manage anxiety while delivering religious messages in digital spaces. The research applies a qualitative library method by reviewing scientific journals, theoretical books, and academic publications on communication psychology and digital media published between 2020 and 2026. Content analysis and hermeneutic criticism are used to interpret the data, while Western communication theories are combined with Islamic interpretative perspectives. The findings show that many preachers experience anxiety that is not merely ordinary nervousness, but may develop into serious psychological pressure. This anxiety is shaped by difficult social situations, external expectations, public judgment, and the visual culture of digital media. Therefore, da’wah activists need to transform their organizational practices by integrating psychological strategies and spiritual values. Cognitive restructuring can help reduce stress, while tawakkal and qaulan sadida strengthen sincerity, ethical speech, and emotional stability. This study proposes an integrative framework for managing internal thought and external communication.